Changes in self-reported and accelerometer-measured physical activity among pregnant TRICARE Beneficiaries - Kinsey Pebley; Gregory Farage; Marion E. Hare; Zoran Bursac; Aline Andres; Sultana Mubarika Rahman Chowdhury; G. Wayne Talcott; Rebecca A. Krukowski (BMC, 2022)
Abstract Background Physical activity is recommended for all pregnant individuals and can prevent excessive gestational weight gain. However, physical activity has not been assessed among military personnel and other TRICARE beneficiaries, who experience unique military lifestyles. The current study assessed physical activity among pregnant TRICARE beneficiaries, both active duty and non-active duty, as measured by accelerometry and self-report data to examine potential predictors of physical activity engagement in the third trimester, and if self-report data was consistent with accelerometry data. We expected having a lower BMI, being active-duty, and having higher baseline physical activity engagement to be associated with higher physical activity at 32-weeks. We also hypothesized that accelerometry data would show lower physical activity levels than the self-reported measure. Methods Participants were 430 TRICARE adult beneficiaries (204 Active Duty; 226 non-Active Duty) in San Antonio, TX who were part of a randomized controlled parent study that implemented a stepped-care behavioral intervention. Participants were recruited if they were less than 12-weeks gestation and did not have health conditions precluding dietary or physical activity changes (e.g., uncontrolled cardiovascular conditions) or would contribute to weight changes. Participants completed self-report measures and wore an Actical Activity Monitor accelerometer on their wrist to collect physical activity data at baseline and 32-weeks gestation. Results Based on the accelerometer data, 99% of participants were meeting moderate physical activity guidelines recommending 150 min of moderate activity per week at baseline, and 96% were meeting this recommendation at 32-weeks. Based on self-report data, 88% of participants at baseline and 92% at 32-weeks met moderate physical activity recommendations. Linear regression and zero-inflated negative binomial models indicated that baseline physical activity engagement predicted moderate physical activity later in pregnancy above and beyond BMI and military status. Surprisingly, self-reported data, but not accelerometer data, showed that higher baseline activity was associated with decreased vigorous activity at 32-weeks gestation. Additionally, self-report and accelerometry data had small correlations at baseline, but not at 32-weeks. Conclusions Future intervention efforts may benefit from intervening with individuals with lower pre-pregnancy activity levels, as those who are active seem to continue this habit. Trial Registration The trial is registered on clinicaltrials.gov (NCT 03057808).